Impact of Deacetylation Degree on Properties of Chitosan for Formation of Electrosprayed Nanoparticles - Hien Thi-Thanh Nguyen; Tinh Ngoc Tran; Anh Cam Ha; Phu Dai Huynh (Journal of Nanotechnology)
Biopolymer of natural origin as chitosan has been studied and applied widely in practice. In the pharmaceutical field, especially, chitosan nanoparticles have been researched for a variety of drug delivery systems. There are many factors influencing the success of the chitosan nanoparticle delivery system. Therein, the specific parameters to the physicochemical nature of chitosan greatly determine the efficiency of its drugs carrier. The degree of deacetylation (DD) of chitosan is one of those parameters. In this study, the influence of DD on chitosan properties was clarified to facilitate the preparation of nanoparticles by the electrospraying method. DD can affect the solubility, crystallinity, and surface tension of chitosan, but it cannot strongly impact the viscosity of chitosan solution as much as the molecular weight (Mv). From these results, M3 chitosan, owning a high DD of 86.70%, and crystalline index of 44%, was dissolved in acetic acid for the collection of electrosprayed nanoparticles. The M3 solution having low viscosity of under 50 mm2/s displayed the easy adjustment of the stable Taylor-cone droplet at the nozzle tip. Particularly, the M3 chitosan solution with a concentration of 1.5 wt.% in acetic acid of 90 wt.% concentration operated at the working condition of 12 kV voltage, a distance between the two electrodes of 10 cm created spherical particles with an average diameter of 338 nm, narrow size distribution. These chitosan nanoparticles can obtain the initial requirement for application as injectable drugs carrier.